Simulation of Fuel Cell Technology Using Matlab - Sheebha Jyothi, G; Bhaskar Rao, Y (International Journal of Engineering and Technology, 2018)
This paper represents a mathematical model for proton exchange membrane fuel cell(PEMFC)system. Proton exchange membrane fuel cell (also called polymer Electrolyte Membrane fuel cells(PEM)) provides a continuous electrical energy supply from fuel at high levels of efficiency and power density. PEMs provide a solid, corrosion free electrolyte, a low running temperature, and fast response to power.Â Â